Anticancer effect of ethanol Lycium barbarum (Goji berry) extract on human breast cancer T47D cell line. Issue 17 (1st September 2016) - Wawruszak, Anna; Czerwonka, Arkadiusz; Okła, Karolina; Rzeski, Wojciech
Abstract: The anticancer activity of ethanol extract isolated from Goji berry (EEGB) on T47D human breast cancer cell line has been reported. Cell viability and cell proliferation were examined with the use of BrdU, MTT and NR methods. Induction of apoptosis was assessed by propidium iodide and Hoechst 33342 staining. Expression of genes involved in cell proliferation, apoptosis, cell cycle control and regulation of transcription was estimated using Western blotting analysis. EEGB inhibited the proliferation of breast cancer cells in a time-, and dose-dependent manner. The study confirmed the lack of EEGB cytotoxic activity to normal human skin fibroblasts. Western blot analysis demonstrated an increase in pro-apoptotic and a decrease in anti-apoptotic proteins' expression in cells treated with the extract. Anticancer activity and lack of toxicity against normal cells indicate a chemopreventive potential of Goji berries in breast cancer treatment. Abstract :